Energy and fluid recovery - Pluim, B. M. (2001)
Energy recovery Studies have consistently shown that carbohydrates consumed immediately before or during exercise enhance performance by increasing glycogen stores, delaying fatigue and enhancing recovery. More specifically, Vergauwen et al.1 showed that carbohydrate supplementation improves stroke performance during the final stages of prolonged tennis play. The researchers tested error rate, ball velocity and the precision of ball placement in 13 male tennis players before and after a strenuous two-hour training session, with and without carbohydrate supplementation. The increase in the error rate and number of non-reached balls in defensive rallies was reduced during carbohydrate supplementation. Similarly, carbohydrates slowed the increase in error rate and the decrease in velocity precision for the service after the onset of fatigue. How much carbohydrate is needed, therefore, and does a regular diet provide enough? Ferrauti and Weber2 of the Institute of Sports in Cologne have shown that, during two hours of strenuous tennis match play, men use approximately 200g of carbohydrates, and women approximately 130g. These needs can be met by consuming a healthy low-fat diet with no more than 30% fat and approximately 55% carbohydrates. However, such a diet may not contain enough carbohydrates for a player who practices up to five hours a day. It may result in gradually diminishing glycogen stores and declining performance during the course of a five-set match. Under these circumstances, extra carbohydrates should be consumed prior to or during play. Suitable on-court snacks include energy bars, which supply plenty of carbohydrates (19g in a 25g bar), as do bananas (one banana contains 20g of carbohydrates). However, bananas take more than two hours to digest, so if more rapid supplementation is needed, it is better to choose a sports drink (20g carbohydrate in 250ml). A Mars bar is not the optimal choice, due to the large amount of fat it contains in addition to the carbohydrates.